PEMBERIAN KOMPOS TKKS DAN COCOPEAT PADA TANAH SUBSOIL ULTISOL TERHADAP PERTUMBUHAN BIBIT KELAPA SAWIT (Elaeis guineensis Jacq.) DI PRE NURSERY - SIZIKO ANDRI; NELVIA NELVIA; SUKEMI INDRA SAPUTRA (Jurnal Agroteknologi, 2016)
Palm oil (Elaeis guineensis Jacq.) is a plantation crop which is quite important in Indonesia because it accounts for foreign exchange and create employment that is high enough. Palm oil empty fruit bunches (EFB) is estimated at 20% of fresh fruit bunches ( FFB ) and coco in (cocopeat) are very much in Riau as raw material for fertilizer / compost. Subsoil ultisol a bottom layer of soil with sufficient depth within therefore very potential as a medium of palm oil nursery but has a low fertility signified by the nature of physics, chemistry and biology poor. Organic matter such as EFB compost and cocopeat can improve physical, chemical and biological subsoil ultisol. The research aimed to study the effect of EFB compost , cocopeat and a mixture of both the subsoil ultisol medium on the growth of palm oil seedlings in pre nursery. The study was conducted at the experimental station of Agriculture Faculty of the University of Riau from June to August , 2015. Research conducted an experiment using a completely randomized design (CRD) consisting of 6 treatments (K0 : without treatment , K1 : 100 g cocopeat , K2 : 100 g compost EFB , K3 : 50 g compost EFB + 50 g cocopeat , K4 : 75 g of compost EFB + 25 g cocopeat and K5 : 25 g compost cocopeat EFB + 75 g per plant) each repeated 4 times. The results showed treament EFB compost 50 g and cocopeat 50 g produce in the growth palm oil seedlings better than the other treatments on medium subsoil ultisol in pre nursery.